2003
DOI: 10.1002/hed.10251
|View full text |Cite
|
Sign up to set email alerts
|

The value of frozen section in intraoperative surgical management of thyroid follicular carcinoma

Abstract: The intraoperative diagnosis of FC is difficult. Although the percentage of false-negative results was relatively high (44.3%), there were no false-positive results. This means that the second operation was avoided in 55.7% of the patients, and no unnecessary thyroidectomies were performed. FS biopsy is an important method in surgery of follicular tumors. Improved technical support and the ability to analyze a greater number of slides will increase the accuracy of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…However, the study evaluated only nine cases of well‐differentiated thyroid cancer with high cost of frozen section. Most studies reported a relatively high (44.3%) percentage of false‐negative results in the diagnosis of follicular thyroid carcinoma by frozen section 14. In contrast, there were very few false‐positive results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study evaluated only nine cases of well‐differentiated thyroid cancer with high cost of frozen section. Most studies reported a relatively high (44.3%) percentage of false‐negative results in the diagnosis of follicular thyroid carcinoma by frozen section 14. In contrast, there were very few false‐positive results.…”
Section: Discussionmentioning
confidence: 99%
“…For some cases of minimally invasive or so-called atypical adenoma the problem of accurate diagnosis still remains. The values of frozen sections in intra-operative surgical management of thyroid follicular carcinoma have been confirmed by most surgeons [17]. With multiple frozen sections, typically 5 to 12 depending on the size of the tumor, the diagnostic accuracy of frozen section is roughly 98% [18,19].…”
Section: Frozen Section For Follicular Thyroid Carcinomamentioning
confidence: 99%
“…A cost-effective analysis for diagnosis of follicular thyroid carcinoma should be conducted in different countries, and if the cost is not higher than a secondary operation, improved technical support and an increased number of slides will increase accuracy of frozen section diagnosis [17]. Frozen section procedures during thyroid surgery, using quick-freezing microtome with a modified toluidine blue staining or standard H&E staining, have been evaluated [17]. There are still problems in interobserver and intraobserver reproducibility in histopatholical diagnoses of follicular thyroid cancer [26].…”
Section: Frozen Section For Follicular Thyroid Carcinomamentioning
confidence: 99%
“…[9] Thus, diagnosis of a solitary encapsulated nodule with follicular histologic pattern is sometimes problematic for pathologists. [5,10] One of the most challenging tasks in pathologic evaluation of thyroid follicular pattern lesion is distinction between FTC and FTA as a common benign thyroid nodule. [4] Diagnosis of carcinoma is based on the presence of capsular, vascular or extra thyroid tissue invasion or nodal or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Diagnosis of carcinoma is based on the presence of capsular, vascular or extra thyroid tissue invasion or nodal or distant metastasis. [5,8,[10][11][12] Different tools such as IHC and molecular profiling have been used to differentiate between benign and malignant follicular neoplasms or differentiating malignant tumor subtypes, [4,9,13] including some angiogenesis factors. [9] Thyroid is rich in vascular network [14] and shows increased vascularity in both non neoplastic and malignant conditions.…”
Section: Introductionmentioning
confidence: 99%